2004
DOI: 10.1002/biof.5520220118
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in human leukemia cells by naturally fermented sugar cane vinegar (kibizu) of Amami Ohshima Island

Abstract: Naturally fermented vinegar such as Kibizu (sugar cane vinegar in Amami Ohshima, Japan), Kurozu (black rice vinegar in Kagoshima, Japan), Kouzu (black rice vinegar in China) and red wine vinegar in Italy had potent radical-scavenging activity analyzed by DPPH method. For the elucidation of food factor for cancer prevention contained in naturally fermented vinegar, the induction of apoptosis in human leukemia cell HL-60 was investigated with sugar cane vinegar Kibizu. Fraction eluted by 40% methanol from Amberl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…For more than 2000 years, vinegar has been used to season and preserve foods, heal wounds, treat infections (Entani et al 1998;Sengun and Karapinar 2004), prevent cardiovascular disease (Kondo et al 2001;Honsho et al 2005), and suppress tumor formation (Mimura et al 2004;Nanda et al 2004). It has been suggested that vinegar reduces the glucose response to a carbohydrate load in subjects with insulin resistance and healthy adults (Carol et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more than 2000 years, vinegar has been used to season and preserve foods, heal wounds, treat infections (Entani et al 1998;Sengun and Karapinar 2004), prevent cardiovascular disease (Kondo et al 2001;Honsho et al 2005), and suppress tumor formation (Mimura et al 2004;Nanda et al 2004). It has been suggested that vinegar reduces the glucose response to a carbohydrate load in subjects with insulin resistance and healthy adults (Carol et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The most important component of vinegar is acetic acid together with small amounts of vitamins, mineral salts, and amino acids. Although vinegar is mainly used for cooking, it is considered to have several effects such as antibacterial (Entani et al 1998;Sengun and Karapinar 2004), cardiovascular protection (Kondo et al 2001;Honsho et al 2005), and antitumor properties (Mimura et al 2004;Nanda et al 2004). Recent studies have shown that intake of vinegar with or after a meal can reduce the post-prandial glucose level (Johnston et al 2004;Östman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The different results likely arise from different sources, fermentation processes, and/or quantity of active components in Kibizu as compared to Kurozu. Furthermore, Mimura et al reported that the lipophilic fraction of Kibizu extracted with 40 % methanol showed potent radical-scavenging and growth inhibition in leukemia cells (Mimura et al 2004). In agreement with those previous results, we also observed strong suppression of lipid accumulation in n-butanol-or diethyl ether-extracted Kibizu fractions, suggesting that similar lipophilic or hydrophobic active components are responsible for these activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SAV is produced from barley, mille, wheat, bran, sorghum, and buckwheat by spontaneous fermentation and SSF. More than 45 compounds are detected in SAV, of which 13 compounds have not been previously reported in other Ghosh et al (2012), Kocher et al (2006), Mimura et al (2004), Giudici (2009), Wu et al (2012b) Starter culture fermentation It increases the safety, the stability, and the efficiency of the process; it reduces production losses caused by uncontrolled fermentation, eliminating undesired features; shortens the fermentation process and reduces the risk of fermentation failure.…”
Section: Relationship Between Microbial Diversity and Other Determinamentioning
confidence: 93%